2008
DOI: 10.1007/s11547-008-0259-4
|View full text |Cite
|
Sign up to set email alerts
|

Work stress in radiologists. A pilot study

Abstract: Radiologists and radiotherapists are exposed to major occupational stress factors, and a significant percentage of them suffer from workplace stress. A special effort is required to prevent this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 44 publications
2
37
0
7
Order By: Relevance
“…Some physician specialties appear to have a relatively low risk of burnout, 12,22 but others may have an enormous problem. 15,31,40,45 Surprisingly, specialties that might be considered high stress because of the nature of the work (surgery, transplantation, or orthopedics) did not report excessively high burnout scores, 12,14,34,38 whereas intensivists and anesthesiologists had a greater incidence. 31,[35][36][37] It seems counterintuitive, but other specialties for which daily work might not at first seem highly stressful (e.g., otolaryngology and radiology) have been at higher risk for burnout.…”
Section: Discussionmentioning
confidence: 95%
“…Some physician specialties appear to have a relatively low risk of burnout, 12,22 but others may have an enormous problem. 15,31,40,45 Surprisingly, specialties that might be considered high stress because of the nature of the work (surgery, transplantation, or orthopedics) did not report excessively high burnout scores, 12,14,34,38 whereas intensivists and anesthesiologists had a greater incidence. 31,[35][36][37] It seems counterintuitive, but other specialties for which daily work might not at first seem highly stressful (e.g., otolaryngology and radiology) have been at higher risk for burnout.…”
Section: Discussionmentioning
confidence: 95%
“…Despite these limitations, the strengths of this study compared to referential international studies 4,15,16) lie in its wide distribution of physician samples include various specialties, plentiful depression risk factors and work condition indicators, and comparisons between JCQ scores with other occupations. Although the results were from survey of volunteer physicians, the major contributions of this pilot study are its reporting of an estimated rate of depression, the status of occupational stress, and the risk and protective factors of depression status among physicians in Taiwan, none of which have been presented before.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians are usually exposed to high levels of occupational stress resulting from heavy workloads and high levels of time pressure, and those in certain employment positions or specialties are at higher risk of suffering from depression disorders than the general population 4,5) . High occupational stress and depression within physicians can even lead to higher suicide ideation or suicide rates 6,7) .…”
mentioning
confidence: 99%
“…Radiologists and radiotherapists are more susceptible to an unpleasant, negative, and non-adaptive reaction to stress (MAGNAviTA et al, 2008). In a research with 136 radiologists in New Zealand, Lim and Pinto (2009) observed that in comparison with physicians practicing in the private service, physicians in the public service presented higher rate of stress and burnout associated to professional dissatisfaction.…”
Section: Studymentioning
confidence: 99%